NK cells contribute to the resolution of experimental malaria-associated acute respiratory distress syndrome after antimalarial treatment - Pollenus, Emilie; Possemiers, Hendrik; Knoops, Sofie; Prenen, Fran; Vandermosten, Leen; Pham, Thao-Thy; Buysrogge, Laura; Matthys, Patrick; Van den Steen, Philippe E. (Frontiers in Immunology, 2024)
In both humans and mice, natural killer (NK) cells are important lymphocytes of the innate immune system. They are often considered pro-inflammatory effector cells, but may also have a regulatory or pro-resolving function by switching their cytokine profile towards the production of anti-inflammatory cytokines, including interleukin-10 (IL-10) and transforming growth factor-β, and by killing pro-inflammatory immune cells. Here, the role of NK cells in the resolution of malaria lung pathology was studied. Malaria complications, such as malaria-associated acute respiratory distress syndrome (MA-ARDS), are often lethal despite the rapid and efficient killing of Plasmodium parasites with antimalarial drugs. Hence, studying the resolution and healing mechanisms involved in the recovery from these complications could be useful to develop adjunctive treatments. Treatment of Plasmodium berghei NK65-infected C57BL/6 mice with a combination of artesunate and chloroquine starting at the appearance of symptoms was used as a model to study the resolution of MA-ARDS. The role of NK cells was studied using anti-NK1.1 depletion antibodies and NK cell-deficient mice. Using both methods, NK cells were found to be dispensable in the development of MA-ARDS, as shown previously. In contrast, NK cells were crucial in the initiation of resolution upon antimalarial treatment, as survival was significantly decreased in the absence of NK cells. Considerably increased IL-10 expression by NK cells suggested an anti-inflammatory and pro-resolving phenotype. Despite the increase in Il10 expression in the NK cells, inhibition of the IL-10/IL-10R axis using anti-IL10R antibodies had no effect on the resolution for MA-ARDS, suggesting that the pro-resolving effect of NK cells cannot solely be attributed to their IL-10 production. In conclusion, NK cells contribute to the resolution of experimental MA-ARDS.